PENGARUH ETIKA, KOMITMEN PROFESIONAL, DAN PERSEPSI KONTROL PERILAKU TERHADAP NIAT MELAKUKAN WHISTLEBLOWING - Florencia Putri Agatha; Lilik Pirmaningsih (CV. Denasya Smart Publisher, 2026)
This study aims to examine and analyze the effect of Ethics, Professional Commitment, and Perceived Behavioral Control on whistleblowing intention. The approach taken in this research is a causal-comparative quantitative approach, focusing on undergraduate accounting students of Universitas Wijaya Kusuma Surabaya (UWKS) from the class of 2022, 2023, and 2024 as the research population. The sample was selected using the purposive sampling method, resulting in 128 respondents, and primary data collection was carried out by distributing questionnaires using a Likert scale. The obtained data were then analyzed using a multiple linear regression analysis technique. The regression model used was declared feasible or fit. Furthermore, the partial analysis results revealed that the variables of Ethics, Professional Commitment, and Perceived Behavioral Control each have a significant and positive effect on whistleblowing intention. The coefficient of determination (Adjusted R Square) value also indicates that these three variables are able to explain 51.4% of the variance in whistleblowing intention. These findings demonstrate that the respondents' willingness to report fraudulent acts (whistleblowing) will increase along with a higher level of ethical understanding, a stronger commitment to the profession, and a higher belief in the behavioral control they possess. The abstract contains a concise and clear description of the research background or urgency, research objectives, applied methods, main findings (as the primary emphasis), and conclusion. The abstract must be written in both Indonesian and English with consistent content, using single spacing, 150–300 words in length, and presented in a narrative form without references, tables, figures, or equations. Following the abstract, 3–5 keywords or key phrases should be provided, separated by commas, representing the research topic, main terms, or important variables, to facilitate indexing and retrieval of the article.